Rapid detection and subtyping of European swine influenza viruses in porcine clinical samples by haemagglutinin‐ and neuraminidase‐specific tetra‐ and triplex real‐time RT‐PCRs. Issue 6 (9th August 2016) - Henritzi, Dinah; Zhao, Na; Starick, Elke; Simon, Gaelle; Krog, Jesper S.; Larsen, Lars Erik; Reid, Scott M.; Brown, Ian H.; Chiapponi, Chiara; Foni, Emanuela; Wacheck, Silke; Schmid, Peter; et al.
Abstract : Background: A diversifying pool of mammalian‐adapted influenza A viruses (IAV) with largely unknown zoonotic potential is maintained in domestic swine populations worldwide. The most recent human influenza pandemic in 2009 was caused by a virus with genes originating from IAV isolated from swine. Swine influenza viruses (SIV) are widespread in European domestic pig populations and evolve dynamically. Knowledge regarding occurrence, spread and evolution of potentially zoonotic SIV in Europe is poorly understood. Objectives: Efficient SIV surveillance programmes depend on sensitive and specific diagnostic methods which allow for cost‐effective large‐scale analysis. Methods: New SIV haemagglutinin (HA) and neuraminidase (NA) subtype‐ and lineage‐specific multiplex real‐time RT‐PCRs (RT‐qPCR) have been developed and validated with reference virus isolates and clinical samples. Results: A diagnostic algorithm is proposed for the combined detection in clinical samples and subtyping of SIV strains currently circulating in Europe that is based on a generic, M‐gene‐specific influenza A virus RT‐qPCR. In a second step, positive samples are examined by tetraplex HA‐ and triplex NA‐specific RT‐qPCRs to differentiate the porcine subtypes H1, H3, N1 and N2. Within the HA subtype H1, lineages "av" (European avian‐derived), "hu" (European human‐derived) and "pdm" (human pandemic A/H1N1, 2009) are distinguished by RT‐qPCRs, and within the NA subtype N1, lineage "pdm" is differentiated. An RT‐PCR amplicon Sanger sequencing method of small fragments of the HA and NA genes is also proposed to safeguard against failure of multiplex RT‐qPCR subtyping. Conclusions: These new multiplex RT‐qPCR assays provide adequate tools for sustained SIV monitoring programmes in Europe.